Effects of dietary garlic supplements on serum lipid profiles, LDL oxidation and weight gain in Western diet-fed rats - Vahidinia, Aliasghar; Komaki, Hojatalah; Rahbani, Mohammad; Darabi, Masoud; Mahjub, Hossein (Progress in Nutrition, 2017)
Background/Objective: Garlic (Allium sativum) has beneficial effects on hypercholesterolemia associated with cardiovascular disease. However, some studies have failed to support the favorable effect of garlic on blood lipid levels. This study was designed to investigate the effect of garlic intake on serum lipids, lipoprotein profiles, low-density lipoprotein (LDL) oxidation and weight gain in rats fed a Western-style diet containing high proportions of fat, cholesterol and refined sugars. Methods: A total of 32 male Wistar rats were divided into four groups and fed one of the following diets for 14 weeks: chow diet (normal control group), Western diet (Western diet control group, WDC) and Western diet including 5% (WD-5G) or 10% garlic (WD-10G). Results: The Western diet significantly increased total cholesterol, LDL cholesterol, non-high-density lipoprotein (non-HDL) cholesterol, atherogenic index and LDL/HDL ratio, and lowered HDL, in comparison to the normal control group. LDL oxidation was increased by the Western diet, and greater differences were observed in group WD-5G vs. group WD-10G. Total cholesterol, LDL cholesterol and non-HDL cholesterol were significantly higher in group WD-10G than in group WDC. Weight gain was significantly lower in both garlic supplementation groups. Conclusion: Our data do not support the beneficial effects of garlic on serum LDL oxidation and lipid profile in rats fed a Western diet. Dietary pattern may be an important factor that influences the atheroprotective properties of garlic.